Analysis and realization of defected ground structure (DGS) on bandpass filter - Khan, M.T. (IEEE Computer Society, 2014)
An end-coupled line bandpass filter (BPF) is proposed and designed by placing defected ground structure (DGS) in the ground plane. DGS is used for its property of miniaturizing the size of microwave filter and also improving the mutual coupling between the resonators. The proposed dumbbell shaped DGS is used to tune the bandpass filter to 2.4 GHz with dimension of 44 mm Ã 18 mm. A wide tuning range of 0.64 GHz is achieved by tuning the height, length and width dimension of DGS unit cell. This filter gives an insertion loss of -0.42 dB, a return loss of -12.31 dB and -3 dB bandwidth of 0.92 GHz. The effect of DGS structure parameters on the frequency of bandpass filter is discussed here. The discussion is concerned over the change in R, L and C parameters of the bandpass filter when defected ground structure is etched in its ground plane. The results conclude that the DGS brings a change in effective inductance and capacitance of a transmission line. Â© 2014 IEEE.